The binding pocket properties were fundamental to functional diversification of the GDSL-type esterases/lipases gene family in cotton - Wang, Jianshe; Zhao, Haiyan; Qu, Yunfang; Yang, Peng; Huang, Jinling (Frontiers in Plant Science, 2023)
Abstract: Cotton is one of the most important crops worldwide. GDSL-type esterases/lipases, are widely present in all kingdoms, and play an important role in regulating plant growth， plant development, and responses to abiotic and biotic stresses. However, the molecular mechanisms behind their functional diversity are still unresolved. Here, based on the identification of the GELP gene family, we applied genetic evolution and molecular simulation techniques to explore the molecular mechanisms in cotton species. There are 1502 GELP genes identified in the 10 cotton species. Segmental duplication and differences in evolutionary rates are the leading causes of increases in the number and diversity of GELP genes during evolution for ecological adaptation. Structural analysis showed that the GELP gene family had high structural diversity. Moreover, molecular simulation studies demonstrated that there were more significant differences in the properties of the binding pockets among cotton GELPs. In the process of adapting to the environment, GELPs not only have segmental duplication, but they also have different evolutionary rates, resulting in gene diversity. This diversity leads to great differences in the 3D structure and the binding pocket properties, and finally to functional diversity. These findings provide references for the further functional analysis of plant GELPs in the future.